Cellular Fiber‐Reinforced Polyurethane Composites with Sensory Properties1. Issue 3 (14th August 2013) - Hufenbach, Werner; Gude, Maik; Geller, Sirko; Stephani, Günter; Scheffler, Michael
<x xml:space="preserve">Abstract</x> The continuing trend towards efficient lightweight solutions is leading to an increasing use of structural components made of fiber‐reinforced polymers (FRP). In order to further increase the lightweight potential, cellular polymers and associated manufacture methods are gaining in importance. Especially for the widespread application of FRP lightweight components, manufacturing technologies suitable for series production are required. Here, the long fiber injection (LFI) process is predestined for the automated fabrication of cellular lightweight structures. The technology is characterized by the processing of expandable polyurethane systems with long fiber reinforcement. The high process variability with locally adaptable fiber lengths and fiber mass contents as well as the various properties of the expandable polyurethane matrix systems offers a wide range of mechanical properties. These can even be improved by the integration of textile reinforcements, for example in sandwich constructions. Beyond weight reduction, there is an increasing demand for the realization and integration of additional functions such as sensory properties. Fiber‐reinforced polyurethane composites offer a great potential for the production of intelligent lightweight structures. Due to its process‐specific advantages like moderate process parameters, the highly productive LFI process is predestined for embedding functional elements like sensors and associated electronic components. Functional elements as well as complete electronic evaluation systems can gently be integrated into the composite.